(untitled) (Texas Journal of Medical Science, 2022)
The article introduces waste-free technology, production of food products of antianemic action by the method of thermoplastic extrusion, food blood of slaughtered animals. The technology of development of these products and the results of their clinical trials are presented. New proposals for the production of an antianemic drug based on raw materials of animal origin for the therapeutic and preventive nutrition of women and children are given.